Ayat-Ayat Tentang Gempa Bumi dalam Al-Qur’an: Analisis Tafsir Ilmi dan Korelasinya dengan Ilmu Seismologi: Penelitian - Iefah Muflihah; Putri Aulia; Aal Mujadilah; Nuzila Khoirun Nisa; Andi Rosa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article explores Quranic verses related to earthquakes through the lens of tafsir ilmi (scientific exegesis) and analyzes their correlation with core concepts in seismology. The study is motivated by the need to integrate revelation and science in addressing natural phenomena comprehensively and contextually. This research employs a qualitative method through literature review, classical and contemporary tafsir analysis, and scientific examination of fundamental seismological theories. The findings reveal that verses such as Surah Az-Zalzalah, Al-Hajj, and An-Nazi’at describe earthquake phenomena in a manner that does not contradict modern scientific explanations, such as tectonic plate movement and seismic waves. Classical interpretations emphasize spiritual and eschatological dimensions, while tafsir ilmi offers a rational and scientific reading. This study concludes that the correlation between the Qur’an and seismology is not aimed at proving the Qur’an through science, but rather at building epistemological coherence that enhances the understanding of ayat kauniyah (signs of nature). This study contributes to the development of integrative Quranic exegesis and encourages ecological awareness among Muslims in responding to natural disasters with both wisdom and scientific insight.